Nutritional evaluation of an improved soybean meal as a fishmeal replacer in the diet of Pacific white shrimp, Litopenaeus vannamei. (29th January 2018) - Hulefeld, Richard; Habte‐Tsion, Habte‐Michael; Lalgudi, Ramanathan S.; McGraw, Barry; Cain, Rob; Allen, Kristy; Thompson, Kenneth R.; Tidwell, James H.; Kumar, Vikas
Abstract: A 12‐week growth trial was conducted to assess an improved soybean meal (ISBM) in the diet of Pacific white shrimp (PWS). Four isonitrogenous and isolipidic experimental diets were formulated: the control diet (ISBM‐0) contained 30% fishmeal (FM) and three test diets (ISBM‐33, ISBM‐66 and ISBM‐100) were formulated by gradually replacing FM on an isonitrogenous basis. Groups of PWS (3.2 g mean initial weight) were fed their respective experimental diets three times per day. Production performance of PWS was unaffected by diet, except the final weight of shrimp‐fed ISBM‐66 diet was significantly lower than those fed ISBM‐0. Whole‐body moisture was significantly higher and protein was significantly lower in PWS‐fed ISBM‐100 versus shrimp‐fed ISBM‐0. PWS‐fed ISBM‐66 had significantly higher oleic acid than shrimp‐fed ISBM‐0 and linolenic acid versus shrimp‐fed ISBM‐0 and ISBM‐100. The lowest linoleic acid and n‐6 polyunsaturated fatty acids levels were found in shrimp‐fed ISBM‐100. Based on second‐degree polynomial regression analysis of final weight and weight gain, the estimated optimum levels of ISBM to replace FM in PWS diets are 89.13% and 95.56% respectively. Overall, results indicate alternative, sustainable, plant‐based protein sources such as ISBM may potentially replace FM in PWS diets.